The value of the (US) democratic Constitution: Reflections on its importance from Alexis de Tocqueville perspective - González Tugas, Juan Andrés (Derecho Público Iberoamericano, 2021)
The existence of a constitution is not in itself a fact that proves democratic order. In this sense, there are constitutions which, despite contemplating a detailed code of conduct or a complete programme of political action, do not meet the necessary and sufficient conditions to allow the subsistence of a political community of free and equal individuals. This paper analyses the value of the Constitution in the context of the institutions that make up the democratic order described by Alexis de Tocqueville.